Preparation of Novel TiO2-g-Polyacrylonitrile Nanocomposites and Their Applications as Ultraviolet Antiaging Agents - Ma, Liqun; Sun, Zhaoyang; He, Zijian; Chen, Guoli; Ao, Lin; Wang, Yazhen (Asian Journal of Chemistry, 2014)
TiO2-g-PAN (PAN = polyacrylonitrile) nanocomposites were synthesized through a surface initiated radical polymerization method, which integrates the advantages of both polyacrylonitrile as a radical scavenger and nanosized rutile-type titanium dioxide (nano TiO2) as an ultraviolet absorber. In this study, the synthetic ultraviolet antiaging agents made of TiO2-g-PAN linked by covalent bonds were prepared via a solution polymerization method, with the optimal synthesis process explored through orthogonal experiments. The nano TiO2-g-PAN particles were characterized by hydrophilic and lipophilic analyses, infrared spectra, energy dispersive spectroscopy, scanning electron microscopy and ultraviolet absorption tests. The nano TiO2-g-PAN particles were blended with polypropylene particles (PP) and the dispersion and antiaging properties of PP/TiO2 and PP/TiO2-g-PAN blends were analyzed. The results showed that the nano TiO2-g-PAN antiaging agent has excellent performances both in dispersion and UV antiaging.